Deformation in the Aravalli Supergroup, Aravalli-Delhi Mobile Belt, NW India and Tectonic Significance - Hahn, Gregor; Kodl, Georg; de Wall, Helga; Schulz, Bernhard; Bestmann, Michel; Chauhan, Narendra Kumar (Structural Geometry of Mobile Belts of the Indian Subcontinent, 2020)
Sediments of the Aravalli Supergroup have acquired a complex superposed fold pattern during Neoproterozoic amalgamation (Grenvillian Orogeny) of north Indian blocks (Marwar block, Bundelkhand craton, North Delhi crustal block) and collision with the Central Indian Craton. The Upper Aravalli metasediments reveal a prograde mono-metamorphic history with continuous increase in metamorphic conditions towards the Delhi Supergroup contact. The transition from phyllites to garnet-bearing mica schist is accompanied by strain increase seen in tightening of F2 folds. Microstructures and deformationmechanism in quartz document an increasing temperature gradient from similar to 280 to 500 degrees C towards the Aravalli-Delhi contact. Garnets, grown prior to the contact-parallel, pervasive second cleavage indicate crystallisation along a prograde P-T-path from 400 degrees C/4 kbar to 500 degrees C/7 kbar. Older metamorphic records in the northern Aravalli-Delhi mobile belt sector (e.g. Sandmata Complex, Mangalwar Complex, and North Delhi Terrane) cannot be related with deformation and metamorphism in the Aravalli Supergroup. Considering the pattern of bivergent thrusts with the Neoproterozoic active continental margin along the western side of the Delhi Fold Belt, the lack of any magmatic signature and the inferred contractional fold and thrust deformation along the eastern proximity can be interpreted as a retro-wedge setting.
CRIS-Team WoS Importer:2021-10-08
Keywords: Aravalli-Delhi contact; Aravalli supergroup; Multiple phases of folding; Quartz microstructure; Garnet thermobarometry; NW India